Pemeriksaan Ante-Mortem Hewan Kurban di Paguyuban Padangaku, Kota Kupang, Nusa Tenggara Timur - Semarabawa, drh. I Gede Semarabawa, M.Si (Lembaga Dongan Dosen, 2023)
The ante-mortem examination of sacrificial animals at Padangaku Association, Kupang City aims to ensure that the sacrificial animals to be slaughtered are only healthy and normal animals. Ante-mortem examination is carried out by inspection. Examinations were carried out on 5 cows and 4 goats. The examination is carried out by observing clinical and pathognomonic symptoms. Inspections are carried out on the attitude and condition of the animal, including nutritional status, respiratory system, digestive system, vaginal openings (mouth, ears, nose, butt), lymph nodes (superficial lymphoglandula), dirt in the eyes, fluid coming out of the eyes (lacrimation ) and runny discharge from the nose. In the ante-mortem examination, no abnormalities or signs of zoonotic infectious diseases were found. The decision taken was in accordance with the results of a series of inspections that had been carried out that all sacrificial animals in the Padangaku Association, Kupang City were permitted to be slaughtered.